Desenvolvimento de método eletroanalítico para determinação direta de cobre em biodiesel e monitoramento do metal em biodiesel exposto a condições simuladas de armazenamento - Almeida, Eduardo Santos (2011)
A simple, effective and low cost for copper determination in biodiesel, without decomposition of the sample is presented. The samples of biodiesel were diluted in a hydro-ethanolic solution (containing HCl as supporting electrolyte) generating a homogeneous ternary system (water-ethanol-biodiesel) in which copper was detected directly using potentiometric stripping constant current using a gold working electrode. The composition of the ternary system was optimized homogeneous aqueous solution of 5 mL 0.1 mol L-1 HCl, 15 mL of ethanol and 0.1 mL (0.088 g) of biodiesel. The detection limit was estimated at 200 ng g-1 (applying deposition time 300 s). In validation tests the method was free from interference, matrix and other metals, and their accuracy was compared with square wave voltammetry with anodic stripping (SWASV) in aqueous solution after extraction of the metal and atomic absorption spectrometry flame (FAAS) after acid mineralization. In another study, the proposed method was applied for copper determination in biodiesel samples exposed to simulated conditions of storage. The samples of biodiesel produced in the laboratory were doped with the antioxidant tert-butyl hydroquinone (TBHQ). The storage conditions were simulated by static immersion corrosion tests in biodiesel (with and without TBHQ) using copper plates. Measures of oxidative stability (induction period by Rancimat) and release the metal in different stages of corrosion were carried out. After 24 h of static immersion test, pure biodiesel and doped with TBHQ had induction times below the limit set by EN 14214 (6 h). The release of copper was more intense in the pure biodiesel (without TBHQ) showing that the corrosion process is delayed in the presence of TBHQ, which acted as a corrosion inhibitor. In parallel, mass spectrometry revealed the presence of considerable amounts of tert-butyl quinone (TBQ) in biodiesel doped with TBHQ and exposed to the etching process. Thus, we do believe that TBHQ molecules adsorb on the copper surface to inhibit corrosion, and then they are catalytically oxidized to TBQ. The results of mass spectrometry also indicated the formation of new molecules of high molecular weight only in the biodiesel doped with TBHQ and deteriorated by the corrosion process. MS-MS spectra provided evidence of the formation of new molecules originated from free radicals of long chain molecules (derived from fatty acids) and TBQ radicals during biodiesel deterioration.